Meninjau Ulang Pandangan Supralapsarianisme Dan Infralapsarianisme: Sebuah Klarifikasi - Manintiro Uling; Rio Janto Pardede; Yatmini Yatmini (Manna Rafflesia, 2022)
The purpose of this article is to review the views of supralapsarianism and infralapsarianism which are two views within the Reformed theology camp. These two views are often misunderstood, supralapsarianism is often seen as making God a sin-maker and God acting unjustly. On the other hand, infralapsarianism is accused of falling on Arminianism. This article is an attempt to clarify the misunderstanding of these two views. The method used in this article is a literature review in the presentation of argumentative main ideas. The results of this study indicate that both supralapsarianism and infralapsarianism cannot be said to be absolute antitheses, but there are also differences that supralapsarianism focuses on the ideal and theological, while infralapsarianism focuses on the historical structure of Bible teachings.